2008
DOI: 10.1007/bf03168232
|View full text |Cite
|
Sign up to set email alerts
|

Pro-antioxidant ratio in healthy men exposed to muscle-damaging resistance exercise

Abstract: The purpose of this study was to compare the pro-antioxidant status in healthy men exposed to muscle-damaging resistance exercise, and to investigate the practical application of Loverro's coefficient (P/A ratio) to evaluate the presence of oxidative stress. Twenty-eight healthy men were assigned to two groups performed multi-joint (M) or single-joint (S) resistance exercise. The activities of superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) as well as the concentration of lipid pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
(29 reference statements)
3
16
0
Order By: Relevance
“…The negative association between physical activity and SOD activity is in agreement with several previous studies [26][27][28], but not with other studies [29,30]. The specific reasons for this inconsistency are still unclear, but could be explained by dynamic response of antioxidants against ROS [31,32].…”
Section: Discussionsupporting
confidence: 87%
“…The negative association between physical activity and SOD activity is in agreement with several previous studies [26][27][28], but not with other studies [29,30]. The specific reasons for this inconsistency are still unclear, but could be explained by dynamic response of antioxidants against ROS [31,32].…”
Section: Discussionsupporting
confidence: 87%
“…This is supported by other studies, which have shown that the total glutathione concentration is not affected by several conditions causing oxidative stress to the muscle fibers [31], whilst cold acclimation can even cause reduction in the total glutathione concentration [32]. On the contrary, exposure to low temperatures [33], hypoxia [34], high altitude [35], exercise [29], and aging [36] are followed by an increase in glutathione peroxidase or glutathione reductase activity in skeletal muscles.…”
Section: Discussionmentioning
confidence: 52%
“…However, recent studies in both humans [44] and animals [34] have shown that exposure to hypoxia caused by high altitude can also lead to the overproduction of ROS and oxidative damage. Similarly, the occlusion of the arterial supply alone caused myopathy with mitochondrial dysfunction and oxidative stress to rats [26].…”
Section: Discussionmentioning
confidence: 99%
“…6 and 7). In acute strength exercises, ROS levels usually rise from their resting levels [30], and there is a close relationship between ROS production and the intensity of exercise [6]. These conditions are with oxidative stress probably caused by oxidizing materials produced in mitochondria or via reperfusion injury [26].…”
Section: Discussionmentioning
confidence: 99%